Peningkatan Keterampilan Membaca Huruf Hijaiyah Menggunakan Metode Tilawati Pada Anak Kelompok A TK 011 Permataku - Sena Bella Mahera; Lusi Marleni; Putri Asilestari (LPPI Yayasan Almahmudi bin Dahlan, 2025)
This study aims to improve the skills of reading hijaiyah letters using the tilawati method in group A children of TK 011 Permataku. The ability to read hijaiyah letters studied is to read hijaiyah letters randomly and distinguish hijaiyah letters that are almost similar. This type of research is class action research. The subjects of this study were 15 group A children consisting of 8 boys and 7 girls. The object of this research is the skill of reading hijaiyah letters using the tilawati method. Data collection techniques through observation and tests. Data analysis techniques carried out descriptively qualitative and quantitative. The success indicator in this study is said to be successful if the ability to read hijaiyah letters with good categories has reached a minimum percentage of 86%. The results showed that the ability to read hijaiyah letters can be improved through the tilawati method. The success is done with steps, reading together using tilawati props, giving children the opportunity to read alone using tilawati tones, giving greater opportunities to children whose improvement in the ability to read hijaiyah letters is still difficult and the teacher motivates and accompanies the child. The increase can be seen from the change in good criteria in each cycle, at the time of pre-action showing the results of 14%, then began to increase in Cycle I by 46% and in Cycle II by 86%.